Pengaruh Perpindahan Panas Pipa Kalor Pada Posisi Horizontal - Ruben Siregar; Rahmat Iman Mainil; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Heat pipes are devices that can transfer heat from one point to another point very quickly at a constant temperature difference, with large heat transfer capacity. Heat pipe used in a wide variety of manufactured products, such as laptops, mobile phones, and others. Solid copper and heat pipes are make to have a diameter of 3/8